2014
DOI: 10.1038/nn.3763
|View full text |Cite|
|
Sign up to set email alerts
|

Orbitofrontal activation restores insight lost after cocaine use

Abstract: Addiction is characterized by a lack of insight into the likely outcomes of one’s behavior. Insight or the ability to imagine outcomes is evident when outcomes have not been directly experienced. Using this concept, work in both rats and humans has recently identified neural correlates of insight in the medial and orbital prefrontal cortices. Here we show that these correlates are selectively abolished in rats by cocaine self-administration. Their abolition was associated with behavioral deficits and reduced s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(77 citation statements)
references
References 49 publications
6
70
1
Order By: Relevance
“…For example, the BLA is not required for using information to support Pavlovian reinforcer devaluation induced by illness when only a single outcome is at stake (Pickens et al, 2003). However there is evidence that the BLA becomes more important when multiple outcomes are used and/or outcome value is manipulated by selective satiation (Johnson et al, 2009). Moreover, it has been shown that gustatory areas just caudal to the OFC exhibit BLA-dependent anticipatory encoding of outcomes (Samuelsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, the BLA is not required for using information to support Pavlovian reinforcer devaluation induced by illness when only a single outcome is at stake (Pickens et al, 2003). However there is evidence that the BLA becomes more important when multiple outcomes are used and/or outcome value is manipulated by selective satiation (Johnson et al, 2009). Moreover, it has been shown that gustatory areas just caudal to the OFC exhibit BLA-dependent anticipatory encoding of outcomes (Samuelsen et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the over-expectation paradigm provides a behavioral setting in which ABL and CeN may function in parallel rather than in serial. One possibility is that the role of CeN in overexpectation reflects the involvement of this area in supporting attentional function (Holland and Gallagher, 1993;Maddux et al, 2007;Calu et al, 2010) rather than any selective role in representing certain types of associative information. Additional studies are required to evaluate these possible explanations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…autonomic activity) that might lead to urges, craving and relapses. Model-based Pavlovian learning, similar to structural studies of the instrumental two-step task, is associated with the rodent OFC and hypothesized to reflect the capacity to integrate outcome expectancies with the associative task structure(73) (74) (44). Rodents trained to self-administer cocaine also…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Similar to the hypoactivity observed in the PrL, cocaine SA also leads to a hypoactivity of pyramidal neurons in the orbitofrontal cortex (OFC; although the underlying mechanisms are different), a locus of decision-making and insight in the brain (Lucantonio et al, 2014). Furthermore, this correlated with a 'lack of insight' in the animals (lack of expectation of a larger reward summation, when two different cues were presented at the same time, as shown by unchanged responding), which was normalized by optogenetic stimulation of the OFC neurons.…”
Section: Drug-induced Neuroplasticitymentioning
confidence: 85%